(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
This article briefly describes zoonyms, their use, also concepts such as zoolexes and a zoonymic vocabulary are also considered. From what language did the word "zoonyms" originate, besides how important is the role of zoonyms in the field of phraseology and linguoculturology. In the end, zoonyms in three dictionaries are compared, such as Russian, British and American.